Design and development of human factors based shoe midsole using additive manufacturing - Rambabu, D.; Hariharan, R; Karthik Nambi, A.; Nataraj, R.; Bhaskar, GB. (International Journal of Engineering and Technology, 2014)
The objective of this research is to design and prototype a shoe midsole which bears enough weight of the wearer and absorbs impact forces, at same time being light weight on the aspect of material used and design. The whole design is based on human factors and requirements which were studied using a survey among a group, based on product development guidelines as a part of product lifecycle management. The design conceptualizes the use of gas as the weight bearer and impact absorber by being compactly pressurized in separate pockets, the pockets are intricately placed to optimize force absorption and maintain stability. The prototype is build using additive manufacturing technique which enabled to design with complexity. Thus a highly comfortable and ergonomically better shoe sole design was achieved; this helped in meeting the customer requirements. Keywords: Shoe Midsole; Human Factors Based Design; Prototyping; Additive Manufacturing.